Novel Carbon Materials in the Cathode Formulation for High Rate Rechargeable Hybrid Aqueous Batteries - Xiao Zhu; Tuan K. A. Hoang; Pu Chen (Energies, 2017)
Novel carbon materials, carbon nanotubes (CNTs) and porous graphene (PG), were exploited and used as conductive additives to improve the rate performance of LiMn2O4 cathode for the rechargeable aqueous Zn/LiMn2O4 battery, namely the rechargeable hybrid aqueous battery (ReHAB). Thanks to the long-range conductivity and stable conductive network provided by CNTs, the rate and cycling performances of LiMn2O4 cathode in ReHAB are highly improved—up to about 100 mAh·g−1 capacity is observed at 10 C (1 C = 120 mAh·g−1). Except for CNTs, porous graphene (PG) with a high surface area, an abundant porous structure, and an excellent electrical conductivity facilitates the transportation of Li ions and electrons, which can also obviously enhance the rate capability of the ReHAB. This is important because the ReHAB could be charged/discharged in a few minutes, and this leads to potential application of the ReHAB in automobile industry.